2010
DOI: 10.1007/s12015-010-9210-x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Induced Pluripotent Stem Cell Lines from Friedreich Ataxia Patients

Abstract: Friedreich ataxia (FRDA) is an autosomal recessive disorder characterised by neurodegeneration and cardiomyopathy. It is caused by a trinucleotide (GAA) repeat expansion in the first intron of the FXN gene that results in reduced synthesis of FXN mRNA and its protein product, frataxin. We report the generation of induced pluripotent stem (iPS) cell lines derived from skin fibroblasts from two FRDA patients. Each of the patient-derived iPS (FA-iPS) cell lines maintain the GAA repeat expansion and the reduced FX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 41 publications
6
82
1
2
Order By: Relevance
“…The iPS (Foreskin) 4 clone 1 and clone 2, abbreviated iPS1 and iPS2 ( 42 ), and the hESC line ENVY (ES Cell International) were cultured as described ( 43,44 ). Neuronal induction by noggin (R and D, 500 ng/ml) was performed as described in ( 11 ).…”
Section: Cell Culture and Neural Induction Of Hpscsmentioning
confidence: 99%
“…The iPS (Foreskin) 4 clone 1 and clone 2, abbreviated iPS1 and iPS2 ( 42 ), and the hESC line ENVY (ES Cell International) were cultured as described ( 43,44 ). Neuronal induction by noggin (R and D, 500 ng/ml) was performed as described in ( 11 ).…”
Section: Cell Culture and Neural Induction Of Hpscsmentioning
confidence: 99%
“…None of these studies have yet successfully recapitulated the specific cerebellar neuronal dysfunction and degeneration known to characterize these conditions. In human iPSC-based studies of FRDA, which is caused by an intronic repeat expansion in the FXN gene encoding Frataxin, disease-relevant phenotypes such as reduced Frataxin mRNA and protein levels as well as mitochondrial defects were observed in cardiomyocytes and peripheral sensory neurons, two of the affected cell types in FRDA [33][34][35][36] . In the case of A-T, chromosomal instability and cell cycle checkpoint defects, resulting from mutations in the ATM gene encoding ataxia-telangiectasia mutated (ATM) protein, have been found to reduce the efficiency of the reprogramming of A-T iPSCs 37 .…”
Section: Disease Modelling Of Cerebellar Ataxiasmentioning
confidence: 99%
“…Apart from one previous study that found disability has an influence on work and social activities for people with FA [28], a comprehensive literature search identified no quality of life studies in FA using standardized measures. In relation to this, Wilson et al [29] analyzed the impact of FA on quality of life, noting that late onset was one of the factors negatively associated with quality of life, but also that there were limitations associated with the use of SF-36 V2 in the FA population [12]. Indeed, Delatycki [30] commented that there is a critical need for accurate measurement tools to detect such subtle benefits but that generic questionnaires, such as the SF-36, may not provide appropriate primary outcome measures in FA clinical trials.…”
Section: Citationmentioning
confidence: 99%
“…For example, the generation of induced pluripotent stem cell lines derived from FA patients, following correction of the mutated gene, could provide a useful source of immune-compatible cells for transplantation therapy [12]. However, rehabilitation and physical therapy still play a dominant role in the clinical management of FA patients [13].…”
Section: Introductionmentioning
confidence: 99%